Freddie Mercury : the great pretender [videorecording (DVD)] - Thomas, Rhys; Thomas, Rhys; Mercury, Freddie (Eagle Vision, 2012)
Freddie Mercury was one of the most charismatic, complex, and fascinating characters in British rock music. The story of Queen is a well known one but this new film focuses on Freddie Mercury and the solo projects he worked on outside of Queen. Using extensive archive footage of interviews with Freddie Mercury, concerts, video shoots, and personal material, much of it previously unseen, along with new interviews with friends and colleagues, a portrait emerges of a man who was very different to his flamboyant onstage public persona.